2023
DOI: 10.1186/s13006-023-00556-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving breastfeeding support through the implementation of the Baby-Friendly Hospital and Community Initiatives: a scoping review

Abstract: Background Improved breastfeeding practices have the potential to save the lives of over 823,000 children under 5 years old globally every year. The Baby-Friendly Hospital Initiative (BFHI) is a global campaign by the World Health Organization and the United Nations Children’s Fund, which promotes best practice to support breastfeeding in maternity services. The Baby-Friendly Community Initiative (BFCI) grew out of step 10, with a focus on community-based implementation. The aim of this scoping… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 182 publications
1
4
0
Order By: Relevance
“…We found that compared with the pre-pregnancy underweight mothers, the normal weight and overweight/obese mothers were more inclined to EBF at six months of age, which was not previously reported. Moreover, excessive gestational weight gain, older maternal childbearing age and cesarean birth were risk factors for EBF at six months of age, which were in accordance with a previous Japanese study [ 51 ]. Nonetheless, further research is warranted to validate the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that compared with the pre-pregnancy underweight mothers, the normal weight and overweight/obese mothers were more inclined to EBF at six months of age, which was not previously reported. Moreover, excessive gestational weight gain, older maternal childbearing age and cesarean birth were risk factors for EBF at six months of age, which were in accordance with a previous Japanese study [ 51 ]. Nonetheless, further research is warranted to validate the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…In summary, to enhance EBF rates, our results underscore the significant impact of SES and the importance of ensuring access to BFHs, especially for those with low SES and in rural areas. Recognizing the pivotal role of birth at a BFH in promoting EBF, BFHI promotion programs targeting low socioeconomic and rural populations could yield substantial public health benefits [ 51 ]. Additionally, there is a need to formulate policies to ensure the effective implementation of EBF, such as making policies encouraging primary hospitals and health centers to achieve BFHI certification and expanding BFH to a larger segment of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions may have great application potential because many areas have community health workers available to provide such counselling. However, while several review articles are available to assess the impact of the Baby Friendly Hospital initiative, few assessed or compared timing, optimal number of visits, or other specifics of peer counsellors and breastfeeding 58,59 …”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, exclusive breastfeeding rates have increased nationally ( 24 ) . National programmes, including the baby-friendly hospital initiative ( 37 ) and the WIC programme, which serves half of the infants in the U.S. ( 37 ) , have been critical in not only increasing breastfeeding initiation rates but also advancing policies and programmes to support continued and coordinated breastfeeding services ( 37 ) . WIC breastfeeding support services and interventions, including text messaging, group education sessions and economic incentives have been effective in improving continuation and intensity of breastfeeding among mothers with limited resources ( 38 ) .…”
Section: Discussionmentioning
confidence: 99%